Digital travel photography digital field guide - Busch, David D. (Wiley Pub., 2006)
"Your digital camera is the perfect travel companion. You don't need to pack extra film, worry about airport scanners, budget for processing costs, or wait until you get home to learn whether you got that once-in-a-lifetime shot. Tuck this book in beside your Frommer's(r) travel guide and you'll have everything you need for fantastic photos-how to watch for the right opportunity, compose the picture, work with lighting-even how to edit and upload from the road"--Resource description page.